Authentic Notarial Deed as Evidence in Civil Court: Implications of Forged Signatures - Agustini, Shenti; Alhakim, Abdurrakhman; Sudirman, Lu (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
A notary is an official who is authorized to make an authentic deed that has legal force when used as evidence in a contract conference. The purpose of this study is to analyze the forgery of signatures on authentic deeds that are used as evidence in a civil trial. The research method used is normative juridical. The results of the study show that there are cases of forgery of authentic deeds that are used as evidence in a civil trial, while the judge in the civil trial only seeks formal truth, not checking the authenticity of the authentic deed data. If there is forgery of an authentic deed, it can go to criminal court. Therefore, in order for the civil trialto run efficiently, the judge in the civil trial should not only seek formal truth, but also material truth by using the judge's belief. Based on the coherence theory, the judge in the civil trial is still given the opportunity to find the law through the interpretation of statutory regulations. Then based on the theory of evidence, judges in civil trials can also use their beliefs which are referred to as material truth.